1999
DOI: 10.1002/(sici)1098-2280(1999)33:2<111::aid-em3>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic alterations in pancreatic cancer: A pooled analysis

Abstract: Both K‐ras and p53 gene mutations are found commonly in pancreatic tumors. Analysis of the mutational patterns may provide insight into disease etiology. To further describe the mutational patterns of pancreatic cancer and to assess the evidence to date, we performed a pooled analysis of the published data on genetic mutations associated with pancreatic ductal adenocarcinoma. We included data from studies that evaluated point mutations in the two genes most studied in pancreatic cancer, K‐ras and p53. A majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…About one‐quarter (24.2%) of tumors from Egyptian patients and 36.7% of tumors from US patients included in this study had both K‐ras and p53 mutations, which was similar to previous studies 32, 41, 42. Blanck et al 42 reported 64% of pancreatic cancer patients with both K‐ras and p53 mutations had the same type of mutation (transition or transversion), which suggested an environmental agent might have acted on both genes in a similar manner, or that the particular DNA base is prone to mutation 42…”
Section: Discussionsupporting
confidence: 87%
“…About one‐quarter (24.2%) of tumors from Egyptian patients and 36.7% of tumors from US patients included in this study had both K‐ras and p53 mutations, which was similar to previous studies 32, 41, 42. Blanck et al 42 reported 64% of pancreatic cancer patients with both K‐ras and p53 mutations had the same type of mutation (transition or transversion), which suggested an environmental agent might have acted on both genes in a similar manner, or that the particular DNA base is prone to mutation 42…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the lack of interaction between smoking and CYP1A1 polymorphisms in this study also suggests that the major mechanism by which smoking increases the risk of pancreatic cancer is not through the direct action of tobacco-associated constituents (e.g., PAH) that are modified by CYP1A1. Further, evidence for a direct effect of smoking on pancreatic cancer risk is not supported by the spectra of p53 and K-ras mutations that are commonly observed in exocrine pancreatic adenocarcinoma (57,58).…”
Section: Discussionmentioning
confidence: 96%
“…The spectrum of p53 mutations in pancreatic adenocarcinoma is mixed in that the number and predominance of transversions of the p53 gene are more similar to those associated with bladder cancer and colorectal cancer than with smoking-related cancers of the lung, head and neck, and esophagus (57,58). In addition, at least 75% of pancreatic tumors show mutations in codon 12 of the K-ras oncogene.…”
Section: Discussionmentioning
confidence: 99%
“…34 Therefore, we also used the AsPC-cell line which harbors a Ki-Ras mutation and has previously been shown to be growth inhibited by ,25(OH) 2 D 3 . 35,36 As shown in Figure 3A, AsPC-cells treated with increasing doses of paricalcitol and ,25(OH) 2 D 3 . were growthinhibited to comparable levels, demonstrating that Ki-Ras mutations do not inhibit the antiproliferative effects of paricalcitol.…”
Section: Paricalcitol and 125(oh) 2 D 3 Induce Similar Anti-prolifermentioning
confidence: 93%